AI and Architecture: Integrating Technology into the Design Process to Realize Gen Z's Revolutionary Ideas through Artificial Intelligence - Umara Hasmarani Rizqiyah; Jusbaeni Jusbaeni; Raeny Tenriola Idrus; Nahridzah Mahjubuh Shibe; Firnawati Firnawati (PT. Global Research Collaboration, 2025)
Artificial Intelligence (AI) has brought significant changes to various creative industries, including architecture. AI can enhance efficiency and creativity in the design process by assisting in data analysis, concept creation, and developing more innovative design variations. Generation Z, born between 1997 and 2012, has great potential to explore this technology due to their adaptive digital skills. However, challenges such as copyright issues and dependence on AI remain concerns in its implementation. This community service activity aims to introduce and educate students and young professionals about the utilization of AI in architecture. The methods used include an introductory session, socialization and workshops, as well as reflection and evaluation. The results of this activity indicate that AI can be an effective tool in architectural design but still requires the role of architects to ensure quality, creativity, and sustainability in design. With the right approach, AI can serve as a catalyst for innovation in the architectural field.